2004
DOI: 10.1104/pp.104.050153
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Deposition Patterns of Recombinant Proteins in Post-Endoplasmic Reticulum Compartments of Wheat Endosperm

Abstract: Protein transport within cereal endosperm cells is complicated by the abundance of endoplasmic reticulum (ER)-derived and vacuolar protein bodies. For wheat storage proteins, two major transport routes run from the ER to the vacuole, one bypassing and one passing through the Golgi. Proteins traveling along each route converge at the vacuole and form aggregates. To determine the impact of this trafficking system on the fate of recombinant proteins expressed in wheat endosperm, we used confocal and electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 46 publications
7
103
0
Order By: Relevance
“…The morphology of the protein bodies of Dx5 transgenic endosperm is similar to that in wheat or barley, in a way that protein bodies are interspersed with a fibrillar matrix Arcalis et al 2004). Beyond normal zein protein bodies, smaller protein bodies occur with the presence of Dx5.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The morphology of the protein bodies of Dx5 transgenic endosperm is similar to that in wheat or barley, in a way that protein bodies are interspersed with a fibrillar matrix Arcalis et al 2004). Beyond normal zein protein bodies, smaller protein bodies occur with the presence of Dx5.…”
Section: Discussionmentioning
confidence: 87%
“…In spite of the divergence in seed storage proteins, however, prolamins from all species accumulate similar ER-derived protein bodies, suggesting that the basic functional interactions required for protein body formation have been preserved across species. Understanding the roles of different prolamins in protein body formation may allow a rational design of cereal products with improved functionality and the production of foreign proteins (Arcalis et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These recombinant proteins are mainly or exclusively deposited into the ER or ER-derived PBs in transgenic cereal seeds, although accumulation sometimes occurs in the PSV instead, due to an interaction between the recombinant protein and endogenous seed proteins. 32,33 When the 7Crp antigen peptide derived from the major T-cell epitopes from Japanese cedar pollen allergens and other types of cytokines, such as IL-4 and IFN-r, were expressed in conjunction with the simultaneous suppression of prolamin genes deposited in ER-derived PB-I, 34 these recombinant proteins were produced at high levels, as was also observed with the production of hIL-10, confirming the efficacy of this technique as a general strategy for increasing the production of recombinant proteins (Fig. 1).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…It has been reported that intracellular deposition is tissue and plant species dependent. [27][28][29] The difference in plant cell types also might affect the presence of protein aggregates. We should examine the differences in character depending on plant cell types to determine the membrane traffic of 11S.…”
Section: )mentioning
confidence: 99%